Armored eyes of the whale shark. - Taketeru Tomita; Kiyomi Murakumo; Shinya Komoto; Alistair Dove; Masakatsu Kino; Kei Miyamoto; Minoru Toda (PLoS ONE, 2020)
This report elaborates on adaptations of the eyes of the whale shark Rhincodon typus (Elasmobranchii, Rhincodontidae), including the discovery that they are covered with dermal denticles, which is a novel mechanism of eye protection in vertebrates. The eye denticle differs in morphology from that of the dermal denticles distributed over the rest of the body, consistent with a different function (abrasion resistance). We also demonstrate that the whale shark has a strong ability to retract the eyeball into the eye socket. The retraction distance was calculated to be approximately half the diameter of the eye, which is comparable to those of other vertebrates that are known to have highly retractable eyes. These highly protective features of the whale shark eye seem to emphasize the importance of vision for environmental perception, which contradicts the general, though poorly established, notion of low reliance on vision in this species.